2022
DOI: 10.3102/0013189x221131505
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Turnover in Early Childhood Education: Longitudinal Evidence From the Universe of Publicly Funded Programs in Louisiana

Abstract: This study uses longitudinal data to follow a cohort ( N = 4,465) of all early childhood education teachers working in publicly funded, center-based settings in Louisiana over a 3-year period. We present the proportion of teachers still at their sites across six time points between 2016 and 2019, providing the first statewide, longitudinal estimates of within-year and multiyear retention. We find that less than 40% teachers in the fall of 2016 are still at their site by the fall of 2019. Turnover is particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Increasing compensation for ECE teachers has been found to significantly reduce teacher turnover (Bassok et al, 2021), which is very high. One recent study found an annual turnover rate of about 40% in the child care sector in Louisiana (Bellows et al, 2021).…”
Section: Implications For Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing compensation for ECE teachers has been found to significantly reduce teacher turnover (Bassok et al, 2021), which is very high. One recent study found an annual turnover rate of about 40% in the child care sector in Louisiana (Bellows et al, 2021).…”
Section: Implications For Familiesmentioning
confidence: 99%
“…Increasing compensation for ECE teachers has been found to significantly reduce teacher turnover (Bassok et al, 2021), which is very high. One recent study found an annual turnover rate of about 40% in the child care sector in Louisiana (Bellows et al, 2021). Reducing turnover leads to more stable environments for children in care, improving child development outcomes (Markowitz, 2019).…”
Section: Implications For Familiesmentioning
confidence: 99%
“…However, interventions by psycho‐educators, along with other professionals, could help reduce socio‐emotional and behavioural problems in childcare settings (Binns et al, 2019; Lanovaz, 2020; Wilburn et al, 2019). Enhanced specialized professional support, especially in the socio‐emotional domain, could reduce the pressure on early childhood educators, which has the potential to reduce the issue of high early childhood educator turnover observed in the last years (Bellows et al, 2022; Schaack et al, 2021). The support from specialized professional in dealing with socio‐emotional issues could also help to reduce child exclusion (Giordano et al, 2022; Mondi et al, 2022; O'Grady & Ostrosky, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, teachers and parents might demonstrate them they can do it and learn new things. According to Bellows et al, (2022), most of them are great oral writers, they can share stories, experiences, opinions, information, big lies and family secrets. That is their way to communicate with others, they would write aloud verbally and spontaneously.…”
Section: Academic Dynamics In First Gradersmentioning
confidence: 99%